Laparoscopic Transabdominal Preperitoneal Repair Is Better Than Open Lichtenstein Hernioplasty in Inguinal Hernia Surgery in Terms of Initial Outcome (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Inguinal hernia is the most commonly done surgery in general surgical practice. Recently laparoscopic techniques (Transabdominal pre peritoneal / totally extraperitoneal approach) are becoming popular than open techniques. Its advantages include decreased hospital stay postoperatively, earlier return to work, decreased postoperative  pain, minimum surgical incisions and so better cosmetic results and lesser postoperative complications. Despite many benefits, laparoscopic  technique have some disadvantage including surgical costs ,  operation time and  instruments facility. To find out a safe and better surgical  technique for inguinal hernia repair and to compare initial outcome of laparoscopic (TAPP) with open Lichtenstein technique for inguinal hernia repair.Materials and methods: This study was conducted in the Department of Surgery, Sylhet MAG Osmani Medical College Hospital (SOMCH) Sylhet. Patient underwent mesh repair of inguinal hernia were enrolled for study and allocated in to two groups, 26 patients in each group. The group-A (Case) treated by laparoscopic Transabdominal preperitoneal repair and group-B (Control) treated by open Lichtenstein hernioplasty.Results: There was no significant difference between two groups in respects to demographic features and ASA status. On comparison between groups, it is evident that frequency of wound infection was 7.2% in group-A. Whereas this frequency was higher, e.g. 30.8% in group B.  Similarly intensity of pain was higher in group-B as compared with group-A. In this study patients in the group-B had higher VAS, during the 1st  POD (p = 0.0001), compared with the group-A. Mean verbal pain score was 5.2±0.47 and 7.4±0.68 in group A & group B respectively. The difference was statistically significant. On 3  POD, both groups showed downward trends of the pain VAS, but significantly in group A. Mean score was 3.1±0.32 and 5.2±0.51 in group A and group B respectively. Therefore it is concluded from the study that Lichtenstein inguinal hernia repair is associated with worse postoperative outcome in the means of wound infection, severe pain and analgesic requirement than laparoscopic TAPP technique.  Present study also shows that duration of hospital stay was  prolonged in group-B (3.1 days vs. 8.5 days in group-A and B respectively), the difference was statistically significant (p < 0.0001).Conclusion: In our study we have come to a conclusion that laparoscopic repair of inguinal hernia have a considerable short term clinical advantage than open hernia repair.JCMCTA 2023 ; 34 (2) : 141-145